Co-existence of Chronic Urticaria and Metabolic Syndrome: Clinical Implications - Ye, Y; Jin, H; Hwang, E; Nam, Y; Kim, J; Shin, Y; Park, H (Acta dermato-venereologica, 2013)
A systemic pro-inflammatory and pro-coagulating state occurs in subjects who have both chronic urticaria and metabolic syndrome. To investigate the prevalence and clinical impact of metabolic syndrome in Korean patients with chronic urticaria, a hospital-based cross-sectional study of 131 patients was performed. Metabolic syndrome was assessed by the criteria of the National Cholesterol Education Program's Adult Treatment Panel III. Urticaria disease activity was assessed by total urticaria activity score (range 0-15). Thirty-nine patients (29.8%) had metabolic syndrome compared to 17.8% in a matched control group (p=0.001). Patients with chronic urticaria and metabolic syndrome were older, had a higher mean urticaria activity score and serum levels of eosinophil cationic protein, tumour necrosis factor-α, and complements, and showed a higher rate of negative autologous serum skin tests compared with those with-out metabolic syndrome. Logistic regression analysis indicated that an urticaria activity score of ≥ 13 (p=0.025) and the presence of metabolic syndrome (p=0.036) were independent predictors of uncontrolled chronic urticaria. We conclude that patients with severe and uncontrolled chronic urticaria should be evaluated for metabolic syndrome in order to reduce cardiovascular risk and improve chronic urticaria outcomes.